Two‐Step Thermal Annealing: An Effective Route for 15 % Efficient Quasi‐2D Perovskite Solar Cells. Issue 8 (5th March 2021) - Romano, Valentino; Najafi, Leyla; Sutanto, Albertus Adrian; Schileo, Giorgio; Queloz, Valentin; Bellani, Sebastiano; Prato, Mirko; Marras, Sergio; Nazeeruddin, Mohammad Khaja; D'Angelo, Giovanna; Bonaccorso, Francesco; Grancini, Giulia
Abstract: Low‐dimensional perovskites (LDP) are nowadays recognized as promising materials for the realization of highly performing photovoltaic cells. However, issues related to film morphology, composition, crystal quality and material homogeneity limit the device performances and reproducibility. In this work, we implement a robust method for the deposition of a LDP mixing methylammonium (MA) and phenylethylammonium (PEA) cations to create the mixed system (PEA)2 MA39 Pb40 I121 by using a two‐step thermal annealing treatment (at 60 and 100 °C). Our approach results in LDP films with high crystal quality and enhanced carrier lifetime, which double the power conversion efficiency of reference devices, reaching up to 15 %. Abstract : Two steps better than one : The use of quasi‐2D perovskites is a promising route towards stable and efficient photovoltaics. Herein, we investigate the (PEA)2 MA39 Pb40 I121 composition, showing that a 2‐step annealing process promotes the formation of a homogeneous perovskite film. The latter is characterized by reduced radiative recombination rates and superior performances compared to perovskite films produced by 1‐step thermal treatment.